Enzymatic degradation of collagen as a factor enhancing calcification of epoxy-treated bioprosthetic heart valves: in vitro modeling data - A. E. Kostyunin; T. V. Glushkova; T. N. Akentyeva; N. N. Borisova; K. Yu. Klyshnikov; P. S. Onishchenko; A. A. Klyueva; E. A. Ovcharenko (Сибирский научный медицинский журнал, 2025)
Aim of the study was to assess in vitro the impact of enzymatic degradation of collagen on the subsequent calcification of the epoxy-treated bovine pericardium used in the production of bioprosthetic heart valves.   Material and methods. The study involved epoxy-treated bovine pericardium patches, samples of which were incubated with bacterial collagenase solution. The degree of degradation of the samples after enzyme treatment was analyzed by mass loss and changes in mechanical properties. The samples were also subjected to proteolysis, and then placed in a calcification solution for 3 weeks. The calcium content was evaluated by spectrophotometry. The control group included epoxy-treated bovine pericardium patches that were not incubated with bacterial collagenase solution.   Results and discussion. On average, the mass loss of studied samples was equal to 8 % during 24-hour incubation in collagenase, which is comparable to the values for glutaraldehyde-treated pericardium according to the literature data. Moreover, the enzyme treatment led to a decrease in the tensile strength of the studied material (14.15 [13.08–16.58; 11.4–22.43] MPa (median [25th percentile – 75th percentile; minimum – maximum]) in control group vs. 10.67 [7.37–11.6; 6.39–11.95] MPa in the study group, p = 0.0003) and increase in its calcification by 1.6 times (8.61 [6.58–9.81; 4.78–14.53] mg of calcium/g of tissue in the control group vs. 13.41 [10.58–17.27; 7.76–28.41] mg of calcium/g of tissue in the study group, p = 0.0001).   Conclusions. The enzymatic degradation of collagen in the epoxy-treated bovine pericardium enhances its calcification in vitro. The data obtained suggest that the accumulation of collagenolytic enzymes in the leaflets of xenopericardial bioprosthetic heart valves is an important mechanism of structural degeneration.